ANALISIS MELODI GAMBUS PADA MUSIK IRINGAN TARI JEPIN SIKANNANG DI DESA SIKANNANG KABUPATEN SAMBAS - Riska Amalia; Yudhistira Oscar Olendo; Asfar Muniir (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The Jepin or Zapin dance represents an example of the adaptation and acculturation process between Islam and local culture that has grown and developed uniquely in Sambas. This research is motivated by the lack of public awareness regarding the arts in Sambas, particularly the Jepin Sikannang dance. The aim of this study is to describe, notate, and analyze the gambus melodies in the musical accompaniment of the Jepin Sikannang dance in Sikannang Village, Sebawi Sambas Regency. The research methodology employed is descriptive and qualitative, supported by a musicological approach. Data collection techniques involve observation, interviews, and documentation, using tools such as observation guidelines, interview guidelines, cameras, sound recorders, and field notes. Data validation is achieved through source triangulation and careful observation. In playing the gambus instrument in the musical accompaniment of Jepin Sikannang, the rhythm and melodic structure serve as an accompaniment to the vocal melody. Based on the analysis, the musical accompaniment of Jepin Sikannang uses the key of Eb=C, employing the C harmonic minor scale consisting of la, si, do, re, mi, fa, sol, and la. The analysis of gambus melodic motifs in the Jepin Sikannang music is guided by 7 theories according to Prier. This research is expected to enhance the knowledge of the younger generation in studying the Jepin Sikannang dance in Sikannang Village, Sebawi Sambas Regency